Recombinant FSH versus hMG in Controlled Ovarian Stimulation for IVF : FSH rekombinan dibandingkan hMG pada stimulasi ovarium terkontrol untuk Fertilisasi in Vitro - Agus Supriyadi; Achmad K. Harzif; Wael O. Al Jaidy (Indonesian Socety of Obstetrics and Gynecology, 2021)
Objectives: To investigate the relationshipxbetween gonadotropins which are used in the process of controlled ovarian stimulation, rFSH and hMG, and the in vitro fertilization outcomes, which are oocyte number, embryo number, and fertilization rate during the period of 2013 to 2019.Methods: This research was a cross sectional study. Data from medical record of patients who underwent the in vitro fertilization procedure at Melati Clinic, Harapan Kita Child and Mother Hospital were obtained. This research collected the oocyte number, embryo number, and fertilization rate of eligible patients who received rFSH or hMG stimulation.Results: Four hundred and fifty four patients were eligible for the research, further divided into 309 patients who received rFSH and 145 patients who received hMG. Non-parametric test revealed that patients who belong to the rFSH group had a statistically significant higher oocyte number, embryo number, and fertilization rate compared to hMG group with p < 0.05.Conclusion: Significant difference of oocyte number, embryo number, and fertilization rate exists between rFSH and hMG group (p < 0.05) with the mean oocyte number, embryo number, and fertilization rate are consistently observed higher in the rFSH group compared to hMG group.Keywords: controlled ovarian stimulation, hMG, infertility, in vitro fertilization, rFSH Abstrak Tujuan: Mengetahui hubungan stimulasi ovarium terkendali yang mendapatkan sediaan gonadotropin berupa rFSH dan hMG dengan luaran FIV berupa jumlah oosit, jumlah embrio, dan tingkat pembuahan pada periode 2013– 2019Metode: Penelitian ini menggunakan desain potong lintang menggunakan data rekam medis yang menjalani program FIV di Klinik Melati Harapan Kita tahun 2013 – 2019. Data yang digunakan adalah data pasien yang menjalani program dengan protokol rFSH dan hMG dibandingkan dengan luaran jumlah oosit, fertilization rate, dan jumlah embrio.Hasil: Dari 454 pasien yang memenuhi kriteria, 309 pasien menggunakan rFSH sebagai obat stimulasi ovarium dan 145 pasien menggunakan hMG sebagai obat stimulasi ovarium. Hasil uji non parametrik lebih tinggi pada kelompok pengguna rFSH dengan ketiga variabel yang diteliti ditemukan bermakna secara signifikan dengan hasil p < 0,05.Kesimpulan: Terdapat perbedaan yang signifikan antara jumlah oosit, tingkat pembuahan, dan jumlah embrio pada kelompok rFSH dan hMG (P < 0,05) dengan rata-rata oosit, tingkat pembuahan, dan jumlah embrio kelompok rFSH lebih besar daripada kelompok hMG Kata kunci: hMG, infertilitas, fertilisasi in vitro, rFSH, stimulasi ovarium